Pernikahan Wisata Perspektif Hukum Islam - Sapri Ali (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Tourist marriage or misyar is illegitimate because it can damage the family and can cause problems in citizenship, because if a man visits four countries and in each country, he has a wife then there will be a mixture of offspring (ikhtilat nasab) which is prohibited by shari'a. Misyar (Tourism) marriage is carried out not based on achieving a purpose of marriage because the marriage is only done to eliminate the value of adultery in the purpose of marriage, but it is still haram because it has a mudharat that will occur in the future. And this marriage only fulfils the concept of maqasid al-shari'ah which is maqashid al-Asl iyyah (the main purpose) but not maqashid tabi'iyah.